The sociology of sport and physical education : an introductory reader - Laker, Anthony, 1951- (RoutledgeFalmer, 2002)
This undergraduate text, written by writers, lecturers and academics in the field, covers the key issues in the field of sociology of sport and physical education. The first section of the text covers the importance of sport in culture, its theoretical background and methodological issues in research. The main body of the book then discusses issues including: gender, the sporting body, race and ethnicity, class, discrimination and stratification, equality, participation and socialization into sport, the hidden curriculum, critical pedagogy, the globalization of sport, sport and the media, and political involvement in physical education, sport and recreation.